Progressive Islam as Muhammadiyah's Response to Modernity: An Ideological Review of the Second Century of MKCH - Pohan, Selamat; Syaiyuti, Amelia Ramdhani; Marpaung, Rizky Arafani Nurhikmah; Syahputra, Mustika Darma; Fauziah, Fauziah; Azziahran, Aliyyah Putri (EDUCTUM: Journal Research, 2025)
This study analyzes the concept of Progressive Islam in Muhammadiyah's Statement of Beliefs and Ideals of Life (MKCH) as an ideological response to the challenges of modernity in the organization's second century. The MKCH, formulated at the 46th Congress in 2010, is a crystallization of Muhammadiyah's progressive thinking that seeks to bridge authentic Islamic values with the needs of the contemporary era. This study uses a qualitative method with a descriptive-analytical approach through content analysis of MKCH documents and related literature. The results show that Progressive Islam in the MKCH represents three main dimensions: first, a theological dimension that emphasizes a substantive-progressive understanding of Islam; second, a methodological dimension that uses a rational-ijtihadi approach in responding to social change; and third, a practical dimension that embodies the values of progress in a social-transformative movement. The transformation of thought in Muhammadiyah's second century shows a shift from a purification movement (tajdid) to a more inclusive and contextual enlightenment movement (tanwir). MKCH is an ideological foundation for Muhammadiyah in facing the complexities of modernity without losing its authentic Islamic identity.